Food as a mechanism of control and resistance in jails and prisons: diets of disrepute - Murguía, Salvador Jimenez (Lexington Books, 2018)
Introduction -- Food as a mechanism of control -- Quality control -- Quantity control -- Food as a mechanism of resistance -- Bricolage -- Survival -- Pleasure -- Conclusion -- Bibliography -- About the author